Local Polarization and Field Induced Anomaly in PLZT Relaxor Ferroelectric Ceramics - Shabbir, G. (The Nucleus, 2015)
Lanthanum doped lead zirconate titanate (Pb1-xLax)(ZryTi1-y)O3 (PLZT x/y/1-y) relaxor ferroelectric ceramics show no macroscopic polarization down to low temperatures as shown by the present dielectric and Raman scattering measurements on PLZT-10/65/35. The measured inverse dielectric constant exhibited a broad minimum that was associated to the randomly oriented local polarization due to appearance of polar nanoregions (PNRs) below the Burns temperature (TB). The temperature dependence of such kind of local polarization was successfully calculated from the classical Landau theory of ferroelectric phase transitions. Electric field induced Brillouin scattering data also exhibited an abnormal shift at ï¾249 K that confirmed the switchable character of local polarization in relaxor ferroelectrics.